Echinocandins - structure, mechanism of action and use in antifungal therapy - Mateusz Szymański; Sandra Chmielewska; Urszula Czyżewska; Marta Malinowska; Adam Tylicki (Taylor & Francis Group, 2022)
With increasing number of immunocompromised patients as well as drug resistance in fungi, the risk of fatal fungal infections in humans increases as well. The action of echinocandins is based on the inhibition of β-(1,3)-d-glucan synthesis that builds the fungal cell wall. Caspofungin, micafungin, anidulafungin and rezafungin are semi-synthetic cyclic lipopeptides. Their specific chemical structure possess a potential to obtain novel derivatives with better pharmacological properties resulting in more effective treatment, especially in infections caused by Candida and Aspergillus species. In this review we summarise information about echinocandins with closer look on their chemical structure, mechanism of action, drug resistance and usage in clinical practice. We also introduce actual trends in modification of this antifungals as well as new methods of their administration, and additional use in viral and bacterial infections.